THE NARRATIVE TECHNIQUES IN THE NOVELS OF TONI MORRIS - Quvatova Mushtariy Farxod qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This paper discusses the narrative styles of the novels of Toni Morrison. The paper is devoted to her attempts at an original application of non-linear form, multiple narration, stream of consciousness, symbolism, myth, oral tradition. The paper uses the analysis of chosen novels and especially Song of Solomon and The Bluest Eye to show how Morrison uses narrative strategies to enhance thematic exploration of identity, trauma, memory, and racial experience. The study reveals that the narrative form in the works of Morrison is not merely a stylistic element but also a cultural and political device to rebuild the marginalized past.